2007
DOI: 10.1016/j.anifeedsci.2006.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Dietary low-phytate mutant-M 955 barley grain alters phytate degradation and mineral digestion in sheep fed high-grain diets

Abstract: Greater production demands for ruminants require increased dietary inclusion of high-energy feeds. Grains and oil seeds are most commonly used to enhance diet energy density. However, use of such feeds proportionally increases the amount of dietary phytate phosphorus (P), which the ruminant may not be able to fully utilise. Our objectives for this study were to determine the extent of phytate degradation and mineral digestion in wethers fed high-grain diets consisting of either a non-mutant or low-phytate muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In sheep consuming high-grain diets, low-phytate barley decreased the amount of undegraded phytate passing into the duodenum compared with conventional barley and increased zinc absorption and retention. This effect was not seen in lambs (Leytem et al, 2007).…”
Section: Phytatesmentioning
confidence: 63%
“…In sheep consuming high-grain diets, low-phytate barley decreased the amount of undegraded phytate passing into the duodenum compared with conventional barley and increased zinc absorption and retention. This effect was not seen in lambs (Leytem et al, 2007).…”
Section: Phytatesmentioning
confidence: 63%
“…However, little work has been done to examine the impact of exogenous phytase on the availability of dietary P in ruminants and the results vary (Hankins-Herr et al, 2009;Long, 2016). Dietary feed type (Leytem et al, 2007), intrinsic phytase of feed ingredients, feed processing (Lakke Gowda et al, 1955;Park et al 2000), passage rate (Kincaid et al, 2005) and forage:concentrate ratios (Bravo et al, 2003) may alter phytate-P hydrolysis in ruminants. Phytase concentration in the rumen was lower in cattle fed grain than those fed forages (Turner and Leytem, 2004).…”
Section: Mineralsmentioning
confidence: 99%
“…Phytase supplementation of dairy cow diets increased phytate hydrolysis and P flow from the rumen to the lower digestive tract and increased faecal excretion of P (Brask- Pedersen et al, 2013). Inorganic P released from phytate may inhibit the activity of phytase due to the presence of excessive substrate, as demonstrated for plant phytases (Gibson and Ullah, 1988;Hubel and Beck, 1996), phytases from Escherichia coli (Greiner et al, 1993), Aspergillus ficuum (Irving and Cosgrove, 1974) and most bacteria (Leytem et al, 2007;Raun et al, 1956 negative impact on phytase production. This unique ability facilitates efficient phytate hydrolysis in the rumen, even when there are high substrate levels in the rumen fluid of animals fed concentrated feed.…”
Section: Mineralsmentioning
confidence: 99%
“…These lines carried mutations in genes encoding enzymes involved in PA biosynthesis, mostly inositol phosphate kinases or myo-inositol phosphate synthases. Feeding trials with poultry [16], swine [17,18], sheep [19], and rats [20] confirmed that lpa barley lines had better nutritional value, with increased mineral and phosphate digestibility. It was observed in previous studies with several lpa mutants that these plants have impaired seed or plant performance [21].…”
Section: Introductionmentioning
confidence: 90%